Thermography is a promising breast cancer detection complementary diagnostic tool - Hassoon Alwan, Mohammed; Qusai Al-Neami, Auns; Hamza Alabedi, Haydar (Edelweiss Applied Science and Technology, 2024)
From the last Twenty years of complying with the strict standardized thermogram interpretation protocols by proper infrared-trained personnel as documented in the literature, breast thermography has achieved high sensitivity and specificity [1]. An abnormal thermogram is reported as the significant biological risk marker for the existence of or continued development of breast tumors. This paper further discusses the implementation, performance, and environmental requirements in characterizing thermography as being used for breast tumor screening under strict indoor controlled environmental conditions. The essential elements of performance requirements include display temperature color scale, display temperature resolution, emissivity setting, screening temperature range, workable target plane, response time, and selection of critical parameters such as uniformity, minimum detectable temperature difference, detector pixels and drift between auto-adjustment. The imaging procedure in this study was carried out at Warith International Oncology Institute